Inovasi Kuliner dan Peluang Bisnis di Era Digital : Studi Partisipatif Lumpia Ubi Ungu - Raymond Larry Ramba; Jenny N. Kaligis; Jessylistina Langie (Global Leadership Organizational Research in Management, 2025)
Lumpia ubi ungu is a modern culinary creation that offers an exclusive taste and accompanying health benefits. In the digital era, business prospects are rapidly increasing, with recipes and marketing concepts readily accessible online. Therefore, consumers can take advantage of this convenience to reach these sellers. Lumpia ubi ungu is a highly appealing dish with a combination of flavors and textures that are entirely different from traditional lumpia. Since it is rich in antioxidants, vitamins, and minerals, lumpia ubi ungu is preferred by health-conscious consumers. There is a growing awareness of healthy food; therefore, lumpia ubi ungu has market potential. Lumpia ubi ungu offers more than just culinary innovation it paves the way for promising business opportunities in this digital era. By adopting the right approach, business players can leverage the wave of health trends and digitalization, thus paving their way to success.